2006
DOI: 10.1007/s10750-006-0240-y
|View full text |Cite
|
Sign up to set email alerts
|

Is there a link between the type of habitat and the patterns of abundance of holothurians in shallow rocky reefs?

Abstract: This paper has not been submitted elsewhere in identical or similar form, nor will be during the first three months after its submission to Hydrobiologia. 2 AbstractThe presence of a mosaic of habitats, largely determined by sea urchin grazing, across shallow rocky reefs may potentially influence in differences in the distribution patterns of invertebrates. The aim of this paper was to assess, using a correlative approach, whether the type of habitat influences the abundance patterns of holothurians in the eas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 36 publications
0
8
0
1
Order By: Relevance
“…This suggests that habitat type is important in determining the abundance of resident snapping shrimp. In contrast, previous studies have shown that macroalgal habitats are more diverse and complex than sea urchin barren habitats (Simenstad et al 1978, Behrens & Lafferty 2004, Graham 2004, Tuya et al 2006. Watanabe et al (2002) used the numbers of snaps produced by snapping shrimp as an environmental monitoring tool and showed that the number of snaps produced in an unpolluted habitat was significantly greater than at a polluted site.…”
Section: Discussionmentioning
confidence: 96%
“…This suggests that habitat type is important in determining the abundance of resident snapping shrimp. In contrast, previous studies have shown that macroalgal habitats are more diverse and complex than sea urchin barren habitats (Simenstad et al 1978, Behrens & Lafferty 2004, Graham 2004, Tuya et al 2006. Watanabe et al (2002) used the numbers of snaps produced by snapping shrimp as an environmental monitoring tool and showed that the number of snaps produced in an unpolluted habitat was significantly greater than at a polluted site.…”
Section: Discussionmentioning
confidence: 96%
“…We determined suitable habitats for each species based on literature (Conand 1998; Tuya et al . 2006; Bellchambers et al . 2011), and in situ habitat description and species occurrence during the surveys.…”
Section: Methodsmentioning
confidence: 99%
“…If appropriate, we used these observations to adjust the habitat zone borders in the GIS. We determined suitable habitats for each species based on literature (Conand 1998;Tuya et al 2006;Bellchambers et al 2011), and in situ habitat description and species occurrence during the surveys. The length-weight relationships for each species were taken from Conand (1989).…”
Section: Generalizing the Assessment Of The Reference Biomass For Mulmentioning
confidence: 99%
“…Some species' tend to occur in aggregations, and their distribution may be influenced by biotic relationships or sediment characteristics (e.g. grain size, organic content) (Conand 1989, Conand & Chardy 1985, Uthicke & Karez 1999, Tuya et al 2006, Shiell & Knott 2010, Slater & Jeffs 2010, Dissanyake & Stefansson 2012. Distribution can also be influenced by other habitat variables such as shelter (Shiell & Knott 2008).…”
Section: Introductionmentioning
confidence: 99%